Flux dynamics and vortex phase diagram of the new superconductor (Li1−xFex)OHFeSe single crystals. (4th July 2017) - Wang, Chunlei; Yi, Xiaolei; Sun, Xiaochen; Tang, Qingbin; Qiu, Yang; Luo, Yongsong; Yu, Benhai
Abstract: Critical current density, transport properties, and magnetic relaxation have been investigated in (Li1− x Fe x )OHFeSe single crystals at different temperatures and magnetic fields. A vortex phase diagram, which shows a large separation between the H c2 and H irr, has been predicated according to the obtained data. The small value of H irr at high temperature as well as the upturn of H irr with the cooling temperature indicates poor flux pinning ability and strong influence of thermal fluctuation. A crossover field H cr, which is located below the irreversibility field and denotes the phase transition from vortex elastic creep to plastic creep, has been identified. H cr is also strongly dependent on the temperature, confirming the influence of thermal activation of flux motion at finite temperature. The large relaxation rate and its strong dependence on magnetic field and temperature have been attributed to thermally activated vortex motion due to a very small flux pinning potential.